Structuring the Flow of Visits to Pangi Beach Tourism Destinations, Blitar Regency through the Preparation of a Blue Print - aji, rojil; Setyowati, Rr. Nani; Bashri, Ahmad (ABISATYA : Journal of Community Engagement, 2023)
Abstract Tourism villages as part of rural life have added many tourists destination options for tourists. Tourist villages have the potential for natural wealth and the cultural life of rural communities. Pangi Beach Tourism Village, which is located in Tumpakkepuh Village, Blitar Regency, has a beautiful beach and several local tourism products in the form of stalls and cafes that offer a variety of beach specialties. Among them are grilled fish, snacks, various traditional Blitar coffees, and fresh young coconut ice. However, there are challenges and problems that are still faced by the Pangi Beach Tourism Village, namely the institutional management of tourist villages and the management of tourist destinations that have not been neatly arranged. Strengthening institutional management between BUM Desa and Pokdarwis as well as village officials is the basis for building competitive tourist villages. Strong institutions and well-organized management of tourist destinations will make Pangi Beach Tourism Village clear and organized. Outcomes of community service activities include online news on activities, journal articles/proceedings, and blueprints for the flow of tourist visits.